A II. világháborút bemutatómúzeumok a békére nevelésért: Stephan Jaeger: The Second World War in the Twenty-First-Century Museum: From Nar-rative, Memory, and Experience to Experientiality. Media and Cultural Memory.Berlin: De Gruyter, Medien und kulturelle Erinnerung Series, 2022. (354o.)ISBN 978-3-11-077770-3 (Training and Practice : Journal of Educational Sciences, 2022)
Stephan Jaeger: The Second World War in the Twenty-First-Century Museum: From Nar-rative, Memory, and Experience to Experientiality. Media and Cultural Memory.Berlin: De Gruyter, Medien und kulturelle Erinnerung Series, 2022. (354 o.) ISBN 978-3-11-077770-3